THE IMPORTANCE OF THE SCHOOL MANAGER IN THE LEARNING PROCESS OF STUDENTS - Ferreira da Silva Dantas, Mônica; Araújo de Lucena, Everaldo (Revista Gênero e Interdisciplinaridade, 2022)
This work consists of a qualitative bibliographic research in which the objective was to recognize the importance of the school manager in the students’ learning process. In order to carry out this research, different readings by specialists in the field of school management were carried out, as well as the LDB approach. Were considered for the theoretical foundation; Lück’s works (2013, 2009); Libâneo et al (2012), (2011); Costa e Silva (1990), among others and the National Education Guidelines and Bases Law, Law No. 9,394 / 96. The discussions carried out in this article show the importance of a managerial work committed to the students’ learning at school and how relevant this professional’s work is in the development of the teaching and learning process in the school environment.